Telecommunication Telepathy: A Meta-Analysis - Sheldrake, Rupert; Stedall, Tom; Tressoldi, Patrizio (Journal of Anomalous Experience and Cognition, 2025)
Objective: We bring together results from 15 published papers describing 26 telecommunication telepathy experiments published between 2003 and 2024 in a meta-analysis to explore the patterns in these results and their overall significance. Methods: The basic experimental design in these experiments involved four potential callers in remote locations. For each trial one of these callers was chosen at random and asked to call the participant, who was on a telephone without a caller ID. The participant then named the caller before answering the phone. Similar experiments were carried out with email and SMS messages. By random guessing, the hit rate would be around 25%. We collected relevant studies from reference lists and online searches and used a random-effects model in the meta-analysis. Results: Overall, hit rates were very significant above chance level (p = 1x10-7). By contrast, in tests carried out under precognitive conditions, the hit rates were at chance. There was no significant difference between the results of Sheldrake and his colleagues, who carried out most of the studies, and independent replications. Selected participants had significantly higher hit rates than unselected participants, and hit rates were significantly higher when callers and participants shared an emotional bond. The effect sizes in telecommunication telepathy are higher than those in ganzfeld and dream telepathy tests. Conclusion: Research on telecommunication telepathy could become an increasingly fruitful area for psi research, especially in conjunction with automated intuition training apps.